Automatic Pricing and Replenishment Decision for Vegetable Commodities Based on Support Vector Regression - Liu, Yiqi; Yi, Siyu; Song, Boxu (Transactions on Economics, Business and Management Research, 2024)
Automated pricing and replenishment decisions for vegetable merchandise play a critical role in the retail industry. Accurate pricing and replenishment forecasts can effectively improve operational efficiency, reduce inventory costs, and increase customer satisfaction. In order to accurately realize the automatic pricing and replenishment decisions, paper use the recent 30-day data to forecast the future based on the cost-plus pricing method, taking into account the seasonality of vegetable commodities, and at the same time, taking into account the cyclicality of vegetable commodities, paper use the sales volume of the previous year in the same month to fit the sales volume of the coming week, and combine the weighting of ARIMA time-series forecasting results to get the final forecasted sales volume, and employ the SUPPORT VECTOR REGRESSION theory to calculate the pricing, using the loss rate to calculate the replenishment, and finally constructed the automatic pricing and replenishment decision model for vegetable commodities applicable to big data, and the results show that the choice of cost-plus ratio is relatively stable, and the standard deviation of the sample is 0.24, which can help hypermarkets to achieve better decision-making.